Analysis of the Existing Fashion Retail Concepts and its Coming Trends - Hoang Vinh, Hien (2012)
The increase of trading has created many environmental, ecological, social and ethical problems. The main concern across all industries is to create more sustainable, eco-friendly and ethical manufacturing processes. Only by influence consumer's purchasing behavior there might be the demand for eco-green products. The fashion and textile industry as one of the main contributor to the world's economy is one of the main environmental polluter (e.g.: soil, lakes, river and air). Recently, many young fashion designers started to offer eco-green fashion to the market. This new phenomenon might change the course of the world fashion industry. The goal of this research is to find out the real demand for eco-green products and its impacts on the traditional methods of fashion manufacturing. Three geographical areas where chosen to represent consumption side (US and EU (UK)) and manufacturing side (China). The specific fashion garment was chosen to demonstrate detailed analysis of the manufacturing processes and its new eco-green formula -- the denim jeans. The primary and secondary research approaches were chosen to cover the whole industrial view on this phenomenon. The outcome of the research showed that the major impact was on the general consumer's purchasing behavior and their life style. It is a new trend and concept that is reshaping the traditional fashion business models. Denim jeans industry leaders such as Levi's Strauss are in process of implementing eco-green, ethical and fair-trade factors into their long-term strategy.